Pengaruh Model Pembelajar Picture and Picture terhadap Hasil Belajar Siswa pada Tema 8 Subtema 1 di Kelas V SD Negeri 173206 Sibingke T.A 2022/2023 - Juliwati E Sianturi; Nurmayani Nurmayani; Daitin Tarigan; Septian Prawijaya; Faisal Faisal (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
The problem in this study is the low learning outcomes of students. The purpose of this study is to determine whether there is a positive influence of the picture and picture learning model on student learning outcomes in theme 8 subtheme 1 in class V SD Negeri 173206 Sibingke. The research used is quantitative research, with a type of quasi-experimental research. The sample of this study was all class V students consisting of two classes, namely class Va as an experimental class and class Vb as a control class. The data collection tool used to determine student learning outcomes is an objective test with a total of 20 questions that have been tested for validation and reliability. The data analysis techniques used are normality test, homogeneity test, and hypothesis test using t-test formula. The results showed that student learning outcomes in theme 8 subtheme 1 increased with picture and picture learning models, namely pretest by 41.25 and posttest by 8. Based on the prerequisites tested first, namely normal and homogeneous data. The results of the normality test and homogeneity test show that the resulting data are normally distributed and homogeneous. The results of the normality test calculation using the Liliefors test obtained student learning results in the experimental class using the picture and picture learning model, namely in the Pre-Test Lcalculate = 0.0926< Ltabel = 0.190 and in the post-test results Lcalculate = 0.155< Ltabel = 0.190 which shows that the data in the experimental class are normally distributed. In the control class using conventional learning models showed that the normality test results in the pre-test were Lcalculate = 0.106< Ltabel = 0.200 and the post-test results showed that Lcalculate = 0.195< Ltabel = 0.200 then the data in the control class were normally distributed. The calculation results of the experimental class and control class pre-test homogeneity test were obtained Fcalculate = 1.194 and the results of the experimental class and control class post-test homogeneity test Fcalculate = 1.115 with Ftable (α = 0.05) obtained 2.243. So Fcalculate< Ftabel concluded that the variance of pre-test and post-test data of experimental and control groups came from homogeneous samples. Furthermore, a hypothesis test was carried out using a t test at the level of α= 0.05, namely Tcalculate > Ttabel or 3.008>1.688 thus Ha was accepted and Ho was rejected so that it can be concluded that: "there is an influence of the picture and picture learning model on student learning outcomes in theme 8 subtheme 1 grade V SD Negeri 173206 Sibingke T.A 2022/2023.